Application of the pedicle screws for cervicothoracic fracture-dislocation - Zhao, Liu-jun; Xu, Rong-ming; Ma, Wei-hu; Jiang, Wei-yu; Xiao, Bai-ping; Ruan, Yong-ping; Sun, Shao-hua; Hu, Yong; Gu, Yong-jie (Zhongguo gu shang, 2009)
To explore pedicle screw implantation for fracture-dislocation injuries at cervicothoracic junction (C6-T2). Pedicle screw implantation was used for twenty-six patients with cervicothoracic fracture-dislocation from May 2001 to Jan 2008. There were 17 males and 9 females with an average of 48.5 years (range,20 to 75 years). Single posterior pedicle screw fixation was performed for 17 cases, and posterior screw fixation combined with anterior reduction and plate fixation for the other nine. The accuracy of the pedicle screws were evaluated by CT views after surgery. Complications and neurological recovery were also recorded after the procedures. All subjects were followed up from 3 to 74 months with average 36.5 months. Four cases of complete paraplegia died of cardiovascular or pulmonary failure within half a year after surgery. There were 104 pedicle screws implanted totallythe including 74 pedicle screws in cervical vertebrae, 16 at C5, 16 at C6, 42 at C7, and 30 pedicle screws in upper thoracic vertebrae,i